Broadband electrostatic noise due to nonlinear electron-acoustic waves - Singh, S.V.; Reddy, R.V.; Lakhina, G.S. (My University, 2001)
Nonlinear propagation of electron-acoustic waves is examined in an unmagnetized, four-component plasma consisting of hot Maxwellian electrons, fluid cold and beam electrons and ions. Solitary structures which are a possible final stage of the electron-acoustic wave growth are obtained. The soliton amplitude and width are numerically obtained. The results are compared with the spiky structures of the broadband electrostatic noise observed in the auroral region of the Earth's magnetosphere. The model predicts parallel electric fields ˜ (10-400) mV/m with typical half widths of the structures ˜ a few Debye lengths.
Keywords: Electron-acoustic waves; Broadband electrostatic noise